2017
DOI: 10.1111/1744-7917.12557
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of honeybee (Apis mellifera) queen, worker and drone larvae by RNA‐Seq

Abstract: Honeybees (Apis mellifera) have haplodiploid sex determination: males develop from unfertilized eggs and females develop from fertilized ones. The differences in larval food also determine the development of females. Here we compared the total somatic gene expression profiles of 2-day and 4-day-old drone, queen and worker larvae by RNA-Seq. The results from a co-expression network analysis on all expressed genes showed that 2-day-old drone and worker larvae were closer in gene expression profiles than 2-day-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 39 publications
5
49
1
Order By: Relevance
“…We asked whether mechanisms identified for maintaining reproductive division of labor in adults also play a role at that stage. While a previous study looking at gene expression during larval caste specification found no differential expression of Dsx (35) , in our experimental perturbation, we found that the gene-level signal was relatively weak ( Figure 1A), possibly due to tissue-specific expression of Dsx (36) , but the network-level signal and its effects were dramatic ( Figure 3A). Therefore we asked whether the Dsx -sensitive module present in adults might also play a similar role in the context of larval caste determination.…”
Section: Does Dsx Play a Role During Larval Caste Differentiation?contrasting
confidence: 73%
See 1 more Smart Citation
“…We asked whether mechanisms identified for maintaining reproductive division of labor in adults also play a role at that stage. While a previous study looking at gene expression during larval caste specification found no differential expression of Dsx (35) , in our experimental perturbation, we found that the gene-level signal was relatively weak ( Figure 1A), possibly due to tissue-specific expression of Dsx (36) , but the network-level signal and its effects were dramatic ( Figure 3A). Therefore we asked whether the Dsx -sensitive module present in adults might also play a similar role in the context of larval caste determination.…”
Section: Does Dsx Play a Role During Larval Caste Differentiation?contrasting
confidence: 73%
“…First, we used an integrated statistic (Z summary ) in the WGCNA package (31) , which tests for preservation of a given module in expression data. According to this test, the Dsx-responsive module detected in our experiment was strongly preserved in whole-body larval gene expression data (35) , meaning that it was also co-expressed in 2 and 4 day old queen-and worker-destined larvae (p = 9.9×10 -7 ). In 4-day old larvae, which have committed to their caste-specific developmental trajectories, these genes were generally upregulated in future queens (rho = 0.083, p = 0.015).…”
Section: Does Dsx Play a Role During Larval Caste Differentiation?mentioning
confidence: 64%
“…We found no significant under or over enrichment in the 100 slowest evolving NCARs. Of the 15,314 genes in the A. mellifera OGS v3.2, 209 were found to be queen-biased and 276 were found to be worker-biased in four day old larvae [22]. Only 16 and 31 NCARs were proximal to queen-and worker-biased genes, respectively.…”
Section: Expression Bias In Foragers and Nursesmentioning
confidence: 95%
“…To investigate the relationship between conserved non-coding regions and genes with castebiased expression in Apis mellifera, we examined genes that are expressed at different levels in virgin queens versus sterile workers for both adults [50] and larvae [51] as well as those differentially expressed between nurses and foragers, which represent categories of age-based worker polyethism [52]. Of the 3,610 genes compared between workers and queen adults, 587 are worker-biased and 649 are queen-biased.…”
Section: Associations Between Ncars and Caste-biased Gene Expressionmentioning
confidence: 99%
“…Finally, within the honey bees, most large studies compare differences between adult bees [50,52], while the NCARs we have identified could affect gene expression at any point throughout development, and it is impossible to predict when, where, and in what context gene expression changes may occur. Although we did examine overlap with genes differentially expressed between worker and queen larvae (Supplementary Information), these results were based on a relatively small dataset and may have only captured those genes with the most extreme expression differences [51].…”
Section: A Subset Of Ncars Are Associated With Gene Expression Differmentioning
confidence: 99%